Modulation of plasma antioxidant activity in weaned piglets by plant polyphenols - Hai J. Zhang; Xian R. Jiang; Graziano Mantovani; Ana E. Valdez Lumbreras; Marcello Comi; Giovanni Alborali; Giovanni Savoini; Vittorio Dell'Orto; Valentino Bontempo (Italian Journal of Animal Science, 2014)
This study was conducted to evaluate the effect of plant polyphenols (PP) on antioxidant activity in weaned piglets. First, a uniform design, one optimising an experimental technique that can rationally arrange the concentrations of mixture components, was used to obtain the best PP mixture of apple, grape seed, green tea and olive leaf polyphenols based on in vitro antioxidant capacity and inhibitory action on bacterial growth. Second, the optimised PP mixture was tested in vivo with an efficacy trial on piglets. The optimal effects of the mix were observed in vitro when apple, grape seed, green tea, olive leaf polyphenols and a carrier (silicon dioxide) accounted for 16.5, 27.5, 30, 2.5 and 23.5%, respectively, of the mixture. Forty-eight weaned piglets were randomly allocated to two dietary treatments (6 replicates of 4 piglets each per treatment) and fed a control diet (CTR) or CTR supplemented with 0.1% of the optimised PP mixture. Dietary PP did not affect growth performance compared to the CTR group. Plasma total protein, urea nitrogen and lysozyme content were not affected by dietary treatment. No differences of E. coli or Clostridia counts in the faeces and caecum content between the CTR and PP groups were observed. A reduced malondialdehyde concentration in the PP group was observed on day 21 compared to the CTR group (P=0.02). In conclusion, the prepared PP mixture has the potential to improve plasma antioxidant activity.